Including Legumes in Bermudagrass Pastures - J. L. Moyer; L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2018)
Bermudagrass is a productive forage species when intensively managed. However, it has periods of dormancy and requires proper management to maintain forage quality. Legumes in the bermudagrass sward could improve forage quality and reduce fertilizer usage; however, legumes are difficult to establish and maintain with the competitive grass. Clovers can maintain survival once established in bermudagrass sod and may be productive enough to substitute for some N fertilization. This study was designed to compare dry cow performance on a bermudagrass pasture system that included ladino and crimson clovers (Legume) vs. bermudagrass alone (Nitrogen).
Keywords: bermudagrass; cows; grazing; crimson clover; ladino clover; wheat; nitrogen